A new snake of the genus Dendrelaphis Boulenger, 1890 (Squamata: Colubridae) from the coastal area of southern Vietnam - Nguyen, Sang Ngoc; Nguyen, Vu Dang Hoang; Le, Manh Van; Nguyen, Luan Thanh; Vo, Thi-Dieu-Hien; Vo, Ba Dinh; Che, Jing; Murphy, Robert W. (Zootaxa, 2023)
We describe a new species of Dendrelaphis from the coastal area in southern Vietnam based on morphological data and nucleotide sequences from one partial mitochondrial gene (Cytb). Dendrelaphis binhi sp. nov. is diagnosed by the following morphological characters: body scale rows 13 at neck and midbody, 9–11 before vent; vertebral scale row feebly enlarged; ventrals 154–158 in males and 161–170 in females; subcaudals 95–106 in males and 95–102 in females; one supralabial touching the eye; 18 or 19 maxillary teeth; hemipenis spinose, reaching 10th or 11th SC, with a slender papilla; cloacal plate divided; dorsum dark brown; and a white stripe along the lower flank. The new species differs from its congeners by an uncorrected p-distance in Cytb sequences of at least 8.1%.